Faktor yang Mempengaruhi Minat Beli Konsumen di Toko Online - Shahnaz, Nanda Bella Fidanty; Wahyono, Wahyono (Management Analysis Journal, 2016)
The purpose of this research is to analyze the effect of reputation, website quality, tand trust on purchase intention at Lazada.co.id online store. The population which is the object of this research is all visitors Lazada.co.id unknown number. The sample in this study were taken by purposive sampling with specific criteria and using the formula of iterations in order to get the number of samples used as many as 100 samples. Data analysis methods used in the study is to perform analysis of the measurement model (outer model) of convergent validity test and reliability test, and analysis of structural models (inner model) and hypothesis testing. The results showed that the variables negatively affect reputation and do not signigikan on purchase intention, but reputation positively affect and significant on purchase intention through trust as a mediating variable; variable of website quality negatively effect and do not significant on puschase intention, but website quality positively effect and significant on purchase intention trhough a trust as a mediating variable. Variable of trust positively effect and significant impact on purchase intention.